Optimalisasi Sistem Pengadaan Jasa dalam Manajemen Logistik PG Kebon Agung Malang - Anggita Savira; Ismi Ifikad (Universitas Kristen Indonesia Toraja, 2024)
Challenges in sugar factory logistics management are often factors that hinder production efficiency and effectiveness. Kebon Agung Sugar Factory is one of the major sugar producers in Indonesia that has an important role in supporting the national sugar industry, a key factor in maintaining competitiveness. In addition, optimization of procurement of goods and services is also closely related to risk management. The implementation of a more modern procurement system is also expected to support aspects of sustainability and resource efficiency. This study uses a descriptive method. Descriptive research with data collection methods used in this study is observation to obtain data regarding the service procurement system at PG Kebon Agung Malang, interviews with Mr. Egi as the head of the logistics sub-section and Ms. Debby as staff in the service procurement sector, and documentation. The system is an important element that a company has to manage all components in the company. Likewise at PG Kebon Agung which has a system that applies to the procurement of goods or services. the service procurement system at PG Kebon Agung Malang has been operating optimally. With the existence of its Own Estimated Price and Service Procurement Request Letter. And after that there will be minutes, aanwijzing, negotiations and finally the process of printing SPK and partner signatures.